EVALUATION OF THE WEBSITES OF THE FIRST-CLASS RESTAURANTS IN TERMS OF DESIGN AND MARKETING ACTIVITIES - Güdük, Tanju; Uca, Selda (Revista de turism - studii și cercetări în turism, 2017)
Websites having attractive, well-designed and sufficient content in terms of design and marketing characteristics influence sales, profitability and consumer satisfaction positively. Therefore it is vitally important for a restaurant to create the design and marketing characteristics of its own web site most efficiently. In this study, the focus is on the evaluation of the websites of first-class restaurants in terms of design and marketing facilities. Content analysis is carried out by using the encoding table consisting of four main themes/categories based on interaction, navigation, functionality (subheadings of ‘design’) and marketing characteristics in websites of 93 first-class restaurants designated as the research sample. In the research, the gathered data is analyzed via SPSS 23 package program. Percentage and frequency analysis which is also called descriptive statistics is used for data interpretation. Obtained findings indicate that the rate of owning a website is low among the restaurants included in the research sample. It has been found that although certain basic features are available in web sites, exclusive features that can affect customer experiences and preferences positively are insufficient in terms of design and marketing characteristics.